Imagem, narrativa e subjetividade: análises político-afetivas em personagens dos filmes de Nelson Pereira dos Santos - Negrini, Márcio Zanetti (2015)
This dissertation aims to investigate the relationship between image, narrative and the political throughout the subjectivity. In this way, a film analysis are developed based on the political-affective aspects of the characters of the films Rio, Zona Norte (1957) and Boca de Ouro (1962) by the director Nelson Pereira dos Santos . The political is treated in cinema from the perspective of Alain Badiou (2004), due to the fact that the characters manifest themselves politically in forms of resistance of dominations of their affections. With this assumption, it is aimed to reflect on how the characters Espírito and Boca de Ouro produce political-affective involvements in their daily lives. For that, a theoretical framework is composed especially by Jacques Rancière (2012), Sigfried Kracauer (2001) e Gilles Deleuze (1985). The analysis show that the political-affective of the characters is formed through fields of force produced by image-narrative interaction. In other words, in one way the image reveals forms of resistance, and the narrative reveals subjections, in another hand the narrative produces senses of resistance and the image reveals stabilization in forms of affective transformation of the characters.